Greek tax policy and macroeconomic framework after the political transition, a systematic approach - Panagiotis ASIMAKOPOULOS (Theoretical and Applied Economics, 2025)

(untitled)
The aim of this paper is to provide with the analysis of Greece taxation trends from 1974 to 2018 concluding on valid results concerning the implemented policies and provide with critical insights to analyze and assess the implementation of the tax policy in a targeted manner and to highlight the main recommendations for policy makers and the tax authorities to further contribute to strategic planning, revenue capacity and efficient tax administration. Furthermore, it is also known from the relevant literature that effective tax rates do not capture only tax changes but the constructed series by tax revenue figures and national accounts considering exemptions, deductions and relevant tax bases to estimate tax burden on an effective way. Thus, we apply Martinez-Mongay method to calculate the effective rates for the examined period and draw conclusions regarding tax policy in Greece.